Algorithmization in Playful Way - Vámosi, Attila (International Journal of Engineering and Management Sciences, 2018)
In the “Extending the Technical Researcher Capacity, Developing Research Services and Building a Knowledge Square in Engineering Education” sub-program of the EFOP-3.6.1-16-2016-00022 "Debrecen Venture Catapult Program" project a research group on engineering and innovation skills was founded. This team undertook to develop skills development workshops for high school students in connection with mathematics, physics, descriptive geometry and informatics topics. In this paper the "Algorithmization in playful way" workshop will be presented, where we develop the student’s algorithmic skills by playing computer games.